Private Law Issues of Concession and Investment within the Framework of Public-Private Partnership - George Khatidze (European Scientific Journal, ESJ, 2018)
Concession is one of the forms of public-private partnership. Financial sources, on the other hand, for many public-private partnership projects are generated by private investment. Both concession and investment play a significant role within the public-private partnership. Analysis of the Law of Georgia on Concession with relevant laws of the other countries clearly underlies that institutional and legal mechanism of concession relations in Georgia do not comply with the best international standards established in many other countries. Law of Georgia on Investment also contains certain shortcomings in that respect. Therefore, it is necessary to improve and further develop private law norms of concession and investment in order to create those institutional and private law basis which are vital for implementation of public-private partnership.